Optimizing Brand Portfolio For Market Competitiveness (A Case Study Of Eiger) - Pratama, Mario; Raafaldini Mirzanti, Isti (Riviera Publishing, 2025)
This thesis explores how optimizing brand portfolio strategy can improve market competitiveness, with EIGER—a leading Indonesian outdoor brand—as the primary case study. As EIGER transitions from a domestic leader to a regional and global contender, the brand faces critical challenges: sub-brand fragmentation, overlapping product lines, diluted brand equity, and operational inefficiencies including oversupply and weak product coordination. Rather than treating brand portfolio and brand architecture as parallel dimensions, this research views them as sequential stages—where a clarified, insight-driven portfolio lays the groundwork for a stronger, more scalable architecture. A well-prioritized brand portfolio, in this context, serves as the strategic bridge between internal clarity and external relevance. Using the Brand Portfolio Audit and Brand Architecture Strategy framework developed by Brandão & Sousa (2020), the research evaluates EIGER’s current portfolio through both quantitative and qualitative lenses—integrating internal brand data, consumer perception analysis, strategic interviews with leadership, and benchmarking against global outdoor and sportswear brands. The analysis identifies structural inconsistencies and disconnects between brand intent and market execution, revealing how ambiguity within the portfolio has weakened both operational focus and consumer resonance. The study proposes a transition from a fragmented sub-brand system to a unified mono-brand architecture anchored on two primary strategic platforms: Outdoor Lifestyle and Outdoor Performance. This model offers a clear structure for category differentiation while leveraging the equity of the master brand. It also enables greater operational efficiency, eliminates redundancy, and enhances emotional connection across market segments. The thesis concludes by outlining a phased implementation roadmap—extending beyond portfolio architecture to include the development of a unified brand identity system, product architecture, and design DNA—positioning EIGER for long-term, scalable growth in a highly competitive global landscape.